2018
DOI: 10.1111/1365-2478.12693
|View full text |Cite
|
Sign up to set email alerts
|

CO2 saturation estimates at Sleipner (North Sea) from seismic tomography and rock physics inversion

Abstract: CO2 saturations are estimated at Sleipner using a two‐step imaging workflow. The workflow combines seismic tomography (full‐waveform inversion) and rock physics inversion and is applied to a two‐dimensional seismic line located near the injection point at Sleipner. We use baseline data (1994 vintage, before CO2 injection) and monitor data that was acquired after 12 years of CO2 injection (2008 vintage). P‐wave velocity models are generated using the Full waveform inversion technology and then, we invert select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 54 publications
(119 reference statements)
0
4
0
Order By: Relevance
“…Seismic methods are widely used for detection and characterization of fluid-saturated porous rocks (Yan et al, 2019). Many studies show that a passing wave loses energy propagating through fluidsaturated rocks (Mavko and Jizba, 1991;Dvorkin et al, 1995;Pride et al, 2004;Müller et al, 2008Müller et al, , 2010Gurevich et al, 2010;Pimienta et al, 2015aPimienta et al, , 2015b.…”
Section: Introductionmentioning
confidence: 99%
“…Seismic methods are widely used for detection and characterization of fluid-saturated porous rocks (Yan et al, 2019). Many studies show that a passing wave loses energy propagating through fluidsaturated rocks (Mavko and Jizba, 1991;Dvorkin et al, 1995;Pride et al, 2004;Müller et al, 2008Müller et al, , 2010Gurevich et al, 2010;Pimienta et al, 2015aPimienta et al, , 2015b.…”
Section: Introductionmentioning
confidence: 99%
“…The parametrization and the associated geophysical observables for the monitor case (partial saturation due to the CO 2 injection) are summarized in Table 1. Part of these rock physics properties can be estimated a priori from geological knowledge, log data or baseline inversions (Yan et al, 2019) as shown in the real data application section.…”
Section: Rock Physics Modelsmentioning
confidence: 99%
“…To obtain the changes in terms of rock physics properties, full‐waveform inversion (FWI) is employed to estimate VP$V_P$ and in the next step, the estimated VP$V_P$ is inverted using rock physics inversion. For example, this two‐step procedure has been used to estimate the changes in the saturation of CO 2 at the Sleipner field in the North Sea (Queißer & Singh, 2013; Dupuy et al., 2016; Dupuy et al., 2016; Yan et al., 2019; Dupuy et al., 2021; Romdhane et al., 2022).…”
Section: Introductionmentioning
confidence: 99%